Disordered Eating: Food and Identity Formation - Kroll, Jeri (The Routledge companion to literature and food, 2018)
As Walter Vandereycken and Ron van Deth assert, the person with an eating disorder is one who engages variously in a "desired or deliberate suppression of appetite and hunger. Eating disorders have developed an international profile in Anglophone countries during the past 40 years. Confessional memoirs, feminist and psychosocial polemics, popular journalism, self-help books, poetry, and fiction have portrayed the emotional and physical effects on individuals, their families, and society of anorexia nervosa and bulimia nervosa. Daughter diminishing of the self through official discourse and interpellation is another feature often associated with eating disorders. Helen Barnes's Killing Aurora embodies adolescent developmental issues: physical, emotional, and intellectual maturation, sexuality, and social integration, within the context of a plot about two 14-year-old reluctant friends, Web and Aurora. Killing Aurora ultimately suggests that friendship can be the most potent agency. Laurie Halse Anderson's Wintergirls embodies eating disorders through a schematic treatment of friendship.